Intermediate pressure reboiling in geothermal flash plant for increased power production and more effective non-condensable gas abatement - Vaclav Novotny; Monika Vitvarova; Jan Spale; Jana Poplsteinova Jakobsen (Energy Reports, 2020)
Non-condensable gases (NCG) in condensing geothermal flash plants have negative effects as they reduce heat transfer and thus deteriorate vacuum in condenser. Therefore, it is necessary to evacuate the condenser by vacuum pumps which substantially increases the parasitic load of the plant. Furthermore, NCG consist mostly of CO2 and H2S, gases for which methods of abatement are being searched for. In such case, further compressors or blowers are usually required to push the gas through absorption systems. Alternative methods of NCG separation consider a reboiler upstream of a turbine. This process is however connected with significant loss of steam enthalpy, moreover the NCG in high content have also certain work potential. Therefore, this method is often not considered as very perspective. We are proposing a novel solution where the turbine is split in two parts at high and low pressure. The splitting point is at a pressure right above an ambient pressure, wherein a reboiler is placed. By doing so the NCG stream is easily obtained without energy penalty of vacuum pumps, without decreasing turbine admission parameters, and also utilizes its pressure potential. This stream is thus easily ready for processing and subsequent CO2 separation and conditioning. Condensed water is from large part turned back to steam in the cold side of reboiler which gives further work in low pressure turbine with achievable lower backpressure and therefore potential for higher power production. Another advantage of this method is liquid phase elimination from the turbine thus achieving higher turbine efficiency.
Keywords: 330; Geothermal; Emissions; CO2; Non-condensable gases; Flash plant; Reboiler